2017
DOI: 10.1038/s41598-017-02019-1
|View full text |Cite
|
Sign up to set email alerts
|

Both haemagglutinin-specific antibody and T cell responses induced by a chimpanzee adenoviral vaccine confer protection against influenza H7N9 viral challenge

Abstract: Since 2013, the outbreak or sporadic infection of a new reassortant H7N9 influenza virus in China has resulted in hundreds of deaths and thousands of illnesses. An H7N9 vaccine is urgently needed, as a licensed human vaccine against H7N9 influenza is currently not available. Here, we developed a recombinant adenovirus-based vaccine, AdC68-H7HA, by cloning the H7N9 haemagglutinin (HA) gene into the chimpanzee adenoviral vector AdC68. The efficacy of AdC68-H7HA was evaluated in mice as well as guinea pigs. For c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
(35 reference statements)
0
13
0
Order By: Relevance
“…Murine peripheral blood mononuclear cells (PBMCs) were isolated as previously described [28]. Splenocytes were isolated from murine spleen by using 100 μm cell strainers, followed by treatment with Ammonium-Chloride-Potassium (ACK) lysis buffer (Beyotime) to remove the red blood cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Murine peripheral blood mononuclear cells (PBMCs) were isolated as previously described [28]. Splenocytes were isolated from murine spleen by using 100 μm cell strainers, followed by treatment with Ammonium-Chloride-Potassium (ACK) lysis buffer (Beyotime) to remove the red blood cells.…”
Section: Methodsmentioning
confidence: 99%
“…The isolated cells were then suspended in complete RPMI-1640 medium (Gibco) and counted for the following experiments. IFN-γ ELISPOT for mice was measured as previously described [28]. Briefly, 96-well PVDF plates (Millipore, Bedford, MA, USA) were pre-coated with 15 μg/ml anti-mouse IFN-γ coating antibody (An-18, Mabtech, Nacka, Sweden) at 4°C overnight, and then blocked with complete RPMI-1640 medium for 2 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…MVA-based vaccines have also been tested in chickens: a MVA-H9 vaccine reduced clinical signs and virus shedding against homologous challenge, but did not prevent infection (Ducatez et al, 2016 ). Other systems using alphavirus, parainfluenza virus, or adenovirus have been developed as influenza vaccine vectors and pre-clinical studies have shown strong induction of anti-HA antibodies and T cell responses and some showed protection against homologous infection (Yang et al, 2009 ; Li et al, 2015 ; Wang et al, 2017 ).…”
Section: Efforts To Avert the Setbacks In Vaccine Usementioning
confidence: 99%
“…The liver and spleen sections were scanned by microscope slide scanner (Pannoramic DESK, 3D HISTECH) and viewed by Caseviewer (C.V 2.3 version). Pathological changes were scored as follows: a score of 1 indicated no pathology, 2 indicated perivascular infiltrates, 3 indicated perivascular and interstitial infiltrates affecting < 20% of the section, 4 indicated perivascular and interstitial infiltrates affecting 20 to 50% of the section, and 5 indicated perivascular and interstitial infiltrates affecting > 50% of the section [ 50 , 51 ].…”
Section: Methodsmentioning
confidence: 99%